Implementation of Reading Characters in BTQ Learning in Elementary - Yudiyanto, Mohamad; Samadi, Mochammad Ramdan; Amaliya, Millati Fitri (Peneliti.net, 2023)
Character education involves conveying important moral and ethical values, such as honesty, cooperation, courage, responsibility, and empathy. The purpose of this study is to elaborate the implementation of reading characters in BTQ learning in elementary. The research method used is library research, data is collected through observation and documentation and analyzed by qualitative analysis. The results show, through intensive reading practice, students can deepen their understanding of the teachings and moral values contained in the Qur'an. Implementing reading characters can also strengthen students' religious identity, so that they feel more connected to the Islamic religion and have a greater awareness of their religious obligations. The love of reading the Qur'an helps shape good character and morals in students, such as patience, honesty, responsibility, and concern for others. Thus, the implementation of reading characters in BTQ learning in elementary schools / MI has a positive impact on the spiritual, moral, and academic development of students, as well as strengthening the foundation of Islam in their lives